Lewis Acid-Promoted Regio- and Diastereoselective Cross-Coupling of Aryl-Substituted 1,2-Diols and Boronic Acids - Yu, Heesun; Lee, Ryangha; Kim, Hyoungsu; Lee, Dongjoo (Journal of Organic Chemistry, 2019)
A Lewis acid-promoted highly regio- and diastereoselective C(sp3)-C(sp2) cross-coupling reaction between unprotected aryl-substituted 1,2-diols and styryl-, aryl-, heteroaryl-, and polyarylboronic acids has been developed in a one-pot procedure. The regioselective opening of aryl-substituted cyclic boronic esters promoted by a Lewis acid followed by subsequent intramolecular 1,4-transfer of the carbon ligand from boron to a resonance-stabilized benzylic carbenium ion minimizing the allylic 1,3-strain in a stereoselective fashion led to the corresponding α-substituted syn-phenylethyl alcohols. The synthetic utility of the method was illustrated by a short and efficient enantioselective synthesis of cherylline diethyl ether (-)-16.
Keywords: Allylic 1 ,3-strain; Cross coupling reactions; Cross-couplings; Diastereoselective; Enantioselective synthesis; One-pot procedures; Stereo-selective; Synthetic utility